SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEGAWAI TELADAN DI UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA DENGAN MENGGUNAKAN METODE TOPSIS - Fadel Muhammad Kemal Pasha (2020)
Employees are one of the important elements of an agency or a company. The good performance of an employee is very beneficial for the company. Recognizing the importance of the quality of employee performance, Universitas Pembangunan Nasional "Veteran" Jakarta as part of an institution within the Ministry of Education and Culture conducted a selection of exemplary employee to spur employee enthusiasm in increasing their dedication and performance. Currently, Universitas Pembangunan Nasional "Veteran" Jakarta has 256 regular academic staff or employees that consist of 53 civil servants, 8 civil servant candidates, and 195 non-civil servants. But with the large number of employees, the exemplary employee selection process is quite complicated and requires careful consideration. It is become a problem whether the chosen candidate of exemplary employees are right person or not. The purpose of this study is to create a decision support system in selecting exemplary employees at Universitas Pembangunan Nasional "Veteran" Jakarta. In doing this research the writer used the TOPSIS method. This method was chosen because the concept is easily understood with computationally efficient and is based on predetermined criteria and weights in order to get more accurate results. The results to be achieved in this research are an application of a decision support system that can help provide alternatives in selecting suitable exemplary employees at the Universitas Pembangunan Nasional "Veteran" Jakarta.